Prevalence, genotyping and risk factors of thermophilic Campylobacter spreading in organic turkey farms in Germany. Issue 1 (December 2016) - Ahmed, Marwa; El-Adawy, Hosny; Hotzel, Helmut; Tomaso, Herbert; Neubauer, Heinrich; Kemper, Nicole; Hartung, Joerg; Hafez, Hafez
Abstract Background The need for organic food of animal origin has increased rapidly in recent years. However, effects of organic animal husbandry on food safety have not been rigorously tested especially in meat turkey flocks. This study provides for the first time an overview on the prevalence and genetic diversity ofCampylobacter species (spp.) in five organic meat turkey farms located in different regions in Germany, as well as on potential risk factors of bacterial spreading. Thirty cloacal swabs as well as water samples and darkling beetles were collected from each flock and examined for the presence ofCampylobacter by conventional and molecular biological methods. The isolates were genotyped byfla A-RFLP. Results Campylobacter spp. were detected in cloacal swabs in all 5 turkey flocks with prevalence ranged from 90.0 to 100 %. 13 cloacal swabs collected from birds in farm III and IV were harboured mixed population of thermophilic campylobacters. In total, from 158Campylobacter isolated from turkeys 89 (56.33 %) were identified asC. coli and 69 (43.76 %) asC. jejuni . ThreeCampylobacter (2C. jejuni and 1C. coli ) were detected in drinkers of two farms and 3C. coli were isolated from darkling beetles of one farm. NoCampylobacter were isolated from main water tanks.fla A-RFLP assay showed that turkey farms can harbour more than one genotype. In a single turkey two different genotypes could be detected. The genotypes of campylobacters isolated from water samples or beetles were identical with those isolated from turkeys. No effect was found of some environmental parameters [ammonia concentration (NH3 ), carbon dioxide concentration (CO2 ), relative humidity (RH) and air temperature)] onCampylobacter prevalence in organic turkey farms. Additionally, drinking water and darkling beetles might be considered as risk factors for the spreading ofCampylobacter in turkey flocks. Conclusions This study highlights the high prevalence and genotypic diversity ofCampylobacter spp. isolated from organic turkey flocks. Further research is needed to assess other potential risk factors responsible for bacteria spreading in order to mitigate the spread ofCampylobacter in organic turkey flocks by improving biosecurity control measures.